APPLICATION OF MODIFYING ALLOYING ALLOY CONTAINING NANOSIZED POWDERS OF ACTIVE ELEMENTS IN PRODUCTION OF HIGH-STRENGTH CAST IRON WITH GLOBULAR GRAPHITE - A. S. Kalinichenko; A. G. Slutsky; V. A. Sheinert (Литьë и металлургия)
Scientific and practical interest is the application of alloying alloy-modifiers for secondary treatment of high-strength cast iron to stabilize the process of spheroidization graphite and achieving higher physical-mechanical properties of castings. The peculiarity of the high-strength cast irons manufacturing technology is their tendency to supercooling during solidification in the mold. This leads to the formation of shrinkage defects and structurally free cementite, especially in thin-walled sections of the finished castings. To minimize these effects in foundry practice during production of ductile iron the secondary inoculation is widely used. In this regard, the question of the choice of the additives with effective impact not only on the graphitization process but also on the formation of the metallic base of ductile iron is relevant. The aim of the present work is to study the peculiarities of structure formation in cast iron with nodular graphite when alloying alloy-modifier based on tin with additions of nanoparticles of titanium carbide, yttrium oxide and graphite nano-pipes is used for secondary treatment. Melting of iron in laboratory conditions was performed in crucible induction furnace IST-006 with an acid lining held. Spheroidizing treatment of melt was realized with magnesium containing alloying alloy FeSiMg7 by means of ladle method. Secondary treatment of high strength cast iron was carried out by addition of alloying alloy-modifier in an amount of 0.1% to the bottom of the pouring ladle. Cast samples for chemical composition analysis, study of microstructure, technological and mechanical properties of the resultant alloy were made. Studies have shown that the secondary treatment of high strength cast iron with developed modifier-alloying alloy results in formation of the perlite metallic base due to the tin impact and nodular graphite with regular shape under the influence of titanium carbide, yttrium oxide and graphite nano-pipes. The tendency of high strength cast iron to «white cast iron» formation has been minimized, and the mechanical properties of the alloy produced correspond to HSCI80.